Exploring antibiotic resistance genes and metal resistance genes in plasmid metagenomes from wastewater treatment plants - Li, An-Dong; Li, Li-Guan; Zhang, Tong (Frontiers in Microbiology, 2015)
Plasmids operate as independent genetic elements in microorganism communities. Through horizontal gene transfer, they can provide their host microorganisms with important functions such as antibiotic resistance and heavy metal resistance. In this study, six metagenomic libraries were constructed with plasmid DNA extracted from influent, activated sludge and digested sludge of two wastewater treatment plants. Compared with the metagenomes of the total DNA extracted from the same sectors of the wastewater treatment plant, the plasmid metagenomes had significantly higher annotation rates, indicating that the functional genes on plasmids are commonly shared by those studied microorganisms. Meanwhile, the plasmid metagenomes also encoded many more genes related to defense mechanisms, including ARGs. Searching against an antibiotic resistance genes (ARGs) database and a metal resistance genes (MRGs) database revealed a broad-spectrum of antibiotic (323 out of a total 618 subtypes) and metal resistance genes (23 out of a total 23 types) on these plasmid metagenomes. The influent plasmid metagenomes contained many more resistance genes (both ARGs and MRGs) than the activated sludge and the digested sludge metagenomes. Sixteen novel plasmids with a complete circular structure that carried these resistance genes were assembled from the plasmid metagenomes. The results of this study demonstrated that the plasmids in wastewater treatment plants could be important reservoirs for resistance genes, and may play a significant role in the horizontal transfer of these genes.